Agricultural distortions and international migration - Britos, Braulio; Hernandez, Manuel A.; Trupkin, Danilo (International Monetary Fund, 2025)
International migration is a recurrent phenomenon that has grown rapidly over the past two decades. This paper examines the role of agricultural distortions in shaping emigration patterns and influencing productivity and welfare in developing countries, using Guatemala as a case study. We develop a theoretical framework where household members can work in agriculture, non-agriculture, or emigrate, and calibrate the model combining detailed micro and aggregate data. Our model identifies two key channels through which agricultural distortions affect migration and productivity: a first channel where distortions increase emigration among more productive agents, reducing aggregate productivity, and a second channel where distortions drive factor misallocation, lowering incomes and increasing overall emigration. Simulations suggest that, reducing distortions in the agricultural sector to the most efficient department in each region would lower the emigrant share by 2.3 percentage points, primarily among more productive workers. Lower distortions would similarly boost aggregate agricultural productivity by 30.1% and raise welfare by 3.4%. An analysis at the sub-national level reveals that high-distortion areas are more isolated and exhibit less financial penetration and government presence.